2016
DOI: 10.1128/jvi.00688-16
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Classical Swine Fever Virus into PK-15 Cells via a pH-, Dynamin-, and Cholesterol-Dependent, Clathrin-Mediated Endocytic Pathway That Requires Rab5 and Rab7

Abstract: Classical swine fever virus (CSFV), a member of the genus Pestivirus within the family Flaviviridae, is a small, enveloped, positive-strand RNA virus. Due to its economic importance to the pig industry, the biology and pathogenesis of CSFV have been investigated extensively. However, the mechanisms of CSFV entry into cells are not well characterized. In this study, we used systematic approaches to dissect CSFV cell entry. We first observed that CSFV infection was inhibited by chloroquine and NH 4 Cl, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 68 publications
3
79
0
1
Order By: Relevance
“…3F). Additionally, the functionality of the Cav1 WT and Cav1 DN constructs was validated in PK-15 cells (Shi et al, 2016). As expected, a significantly decrease of VP1 protein expression level was observed for Cav1 DN construct-transfected cells compared to pEGFP-N1 vector or WT construct-transfected cells (Fig.…”
Section: Psv Entry Depends On Caveolae-mediated Endocytosis and Fluidsupporting
confidence: 70%
See 2 more Smart Citations
“…3F). Additionally, the functionality of the Cav1 WT and Cav1 DN constructs was validated in PK-15 cells (Shi et al, 2016). As expected, a significantly decrease of VP1 protein expression level was observed for Cav1 DN construct-transfected cells compared to pEGFP-N1 vector or WT construct-transfected cells (Fig.…”
Section: Psv Entry Depends On Caveolae-mediated Endocytosis and Fluidsupporting
confidence: 70%
“…2E). The functionality of Eps15 WT and EPS15 DN constructs was confirmed in PK-15 cells by using labeled transferrin as a control (Shi et al, 2016). We then examined PSV infections of cells overexpressing the Eps15 WT and Eps15 DN constructs and no effect was observed on PSV VP1 production with any of the constructs (Fig.…”
Section: Clathrin Is Not Required For Psv Entry In Pk-15 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The confocal results showed that the Vero and IPEC-J2 cells overexpressing wild-type dynamin II (GFP-Dyn-WT) were infected with PEDV while the cells overexpressing mutant dynamin II (GFP-Dyn-M) were barely infected ( Figure 2B). siRNA interference was also used to identify the importance of dynamin II on virus entry [23,35,42]. Sus scrofa and Chlorocebus sabaeus siRNAs of dynamin II (siDyn) were designed and synthesized.…”
Section: Pedv Entry Involves Dynamin IImentioning
confidence: 99%
“…Rab proteins play major roles in endocytic vesicle trafficking (34). Of these, Rab5 is involved in the life cycles of multiple viruses in the family Flaviviridae and is an important factor in the process of CSFV endocytosis (35). Here, we tested whether overexpression of Mx protein affects CSFV endocytosis.…”
Section: Figmentioning
confidence: 99%